IMPLEMENTASI KEPEMIMPINAN, BUDAYA, DAN NETWORKING DALAM MENDETEKSI STARTUP PERFORMANCE MELALUI ORGANIZATIONAL AGILITY - Nurlaila Maysaroh Chairunnisa (UNIVERSITAS INDRAPRASTA PGRI, 2023)
This study aims to empirically examine the implementation of transformational leadership, organizational culture, and networking in detecting stratup performance with organizational agility as an intervening variable. This research will use primary data. Transformational leadership, organizational culture, networking, startup performance, and organizational agility will be measured using a questionnaire which will be distributed using the Google form. The object of this research is startups in Indonesia. The sampling method in this study was purposive sampling with startup criteria that were more than one year old and the respondents were startup employees. This research will use SEM PLS data processing software. The results of this study transformational leadership, organizational culture, networking, and organizational agility have a significant positive effect on startup performance. Meanwhile, transformational leadership, organizational culture, and networking have no effect on startup performance. The results of the path analysis show that transformational leadership cannot indirectly affect startup performance, while organizational culture and networking can indirectly affect startup performance.